Synthesis of Tribological WS2 Powder from WO3 Prepared by Ultrasonic Spray Pyrolysis (USP) - Nataša Gajić; Željko Kamberović; Zoran Anđić; Jarmila Trpčevská; Beatrice Plešingerova; Marija Korać (Metals, 2019)
This paper describes the synthesis of tungsten disulfide (WS2) powder by the sulfurization of tungsten trioxide (WO3) particles in the presence of additive potassium carbonate (K2CO3) in nitrogen (N2) atmosphere, first at lower temperature (200 °C) and followed by reduction at higher temperature (900 °C). In addition, the ultrasonic spray pyrolysis of ammonium meta-tungstate hydrate (AMT) was used for the production of WO3 particles at 650 °C in air. The HSC Chemistry® software package 9.0 was used for the analysis of chemistry and thermodynamic parameters of the processes for WS2 powder synthesis. The crystalline structure and phase composition of all synthesized powders were analyzed by X-ray diffraction (XRD) measurements. The morphology and chemical composition of these samples were examined by scanning electron microscopy (SEM) combined with energy dispersive X-ray analysis (EDX).